Clinical characteristics and risk factor analysis of recipients with multidrug-resistant bacterial bloodstream infections after liver transplantation: a single-centre retrospective study - Chuanlin Chen; Qinghua Guan; Desheng Li; Bo Sheng; Zhenyu Zhang; Yongfang Hu (Taylor & Francis Group, 2024)
Background The clinical characteristics and associated risk factors for recipients who experience multidrug-resistant organism (MDRO) bloodstream infections after liver transplantation are poorly understood. This study aimed to analyse the clinical characteristics and epidemiology of pathogenic bacteria and identify associated risk factors in patients who underwent MDRO after liver transplantation.Method We retrospectively collected data on recipients who developed bloodstream infections after liver transplantation between 2018 and 2023. Recipients were divided into MDRO and non-MDRO groups based on blood culture results. We explored the risk factors for MDRO bloodstream infections post-transplantation and summarised the clinical features, pathogen epidemiology, and prognosis. A multivariate logistic regression analysis was conducted to identify significant risk factors.Results A total of 463 liver transplant recipients were studied, and 73 developed blood infections. There were 29 MDRO cases. The mean duration of the episodes was 26 days (range: 1-474 days). Among these patients, 22 (30.1%) developed blood infections without fever (temperature < 37.3°C), and 33 patients (45.2%) had a white blood cell count between 4 and 10 × 10⁹/L. Among the 108 positive blood cultures, 29 genera were detected, predominantly gram-negative bacilli (n = 64, 58.2%). The detection rate for multidrug-resistant bacilli was 31.8% (35/110), with the abdomen being the most common site of origin (21.3%). Factors such as a history of preoperative intensive care unit (ICU) hospitalisation (p < 0.001) and a preoperative international normalised ratio (INR) > 2 (p < 0.048) were identified as risk factors in multivariate regression analysis.Conclusion Multidrug-resistant bacterial bloodstream infections after liver transplantation tend to occur early in the postoperative period (<30 days) and are associated with high mortality and a lack of specific clinical manifestations. A history of preoperative intensive care unit (ICU) hospitalisation and an international normalised ratio (INR) > 2 may be risk factors for multidrug-resistant bacterial bloodstream infections after liver transplantation.